2008
DOI: 10.5005/jcdp-9-1-38
|View full text |Cite
|
Sign up to set email alerts
|

Instability of Self-esteem and Affective Lability as Determinants of Self-reported Oral Health Status and Oral Health-related Behaviors

Abstract: Aim The aim of the study was to examine the impact of the instability of self-esteem and affective lability on students’ self-rated oral health and oral health-related behaviors. Methods and Material The present study sample consisted of 178 first year medical students. A questionnaire was used to collect information about socio-demographic factors, behavioral factors, self-reported oral health status, the instability of self-esteem, and affective lability. Results Significant differences were found on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 41 publications
2
19
0
1
Order By: Relevance
“…The present study confirmed findings from the previous research (37) examining the role of instability of self‐esteem, self‐confidence, self‐liking, self‐competence, self‐control and perfectionism in self‐rated oral health status and behaviour in samples of first‐year students. Significant differences on the instability of self‐esteem were reported on the following variables: number of extracted teeth and satisfaction with appearance of one’s own teeth.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The present study confirmed findings from the previous research (37) examining the role of instability of self‐esteem, self‐confidence, self‐liking, self‐competence, self‐control and perfectionism in self‐rated oral health status and behaviour in samples of first‐year students. Significant differences on the instability of self‐esteem were reported on the following variables: number of extracted teeth and satisfaction with appearance of one’s own teeth.…”
Section: Discussionsupporting
confidence: 91%
“…Significant differences on the instability of self-esteem were reported on the following variables: number of extracted teeth and satisfaction with appear- ance of one's own teeth. The level of instability of self-esteem had a consistent association with the self-reported oral health status and satisfaction with appearance of teeth (37). In a sample consisted of 217 first-year dental students, significant differences were found by Dumitrescu et al (38) on self-liking and self-competence scales according to several variables: perceived dental health, current non-treated caries, current extracted teeth, satisfaction by the appearance of own teeth, the last time toothache occurred, self-reported gingival condition and self-reported gum bleeding.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Multiple interrelated factors have been considered in an effort to explain this relationship. It was previously reported that the side effects of their medications, poor dental hygiene and smoking caused severe periodontal disease in psychiatric patients (11). In addition, dental treatment is difficult for these patients because of their lack of motivation, limited cooperation, low adaptability to new prostheses, mobility difficulties, fear of treatment, poor communication and financial considerations (11).…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence suggesting that children’s affective and physical feeling states can vary considerably across each day (Axelson et al 2003; Larson & Lampman-Petraitis, 1989). Also, the degree of within-person (i.e., intraindividual) variability in affect over time is related to important physical and psychological health outcomes (Dumitrescu, Dogaru, & Dogaru, 2008; Weinstein, Mermelstein, Shiffman, 2008). Cross-sectional studies or intervention studies with pre-post measurements designs cannot adequately capture intraindividual variability (i.e., the degree of instability) in affective and physical feeling states.…”
mentioning
confidence: 99%